Вечера на хуторе близ Диканьки - Гоголь Николай Васильевич (ЭКСМО, 2014)
7-9 классы. Экземпляры: ФО-7 (20151208) / Инвентарный номер: 48793z1 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Г 58 / ББК: 84(2Рос=Рус)1